2021
DOI: 10.1016/j.anai.2021.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and economic burden of severe asthma among US patients treated with biologic therapies

Abstract: Background: Patients with severe asthma may remain uncontrolled despite biologic therapy in addition to standard therapy, but this disease burden has not been quantified. Objective: To estimate the clinical and economic burden in a US national sample. Methods: Patients who have severe asthma with indicated biologic treatment (earliest use = index date) were selected from the MarketScan database between January 1, 2013, and June 30, 2018. Inclusion criteria were continuous enrollment for 12 months postindex wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 40 publications
(44 reference statements)
0
19
0
Order By: Relevance
“…Our results are in line with a comprehensive evaluation carried out in the United States on complementary therapies with biological drugs in which it was reported that 63% of patients (n = 3262) presented at least one asthma exacerbation per year (M = 1.3). 29 Taken together, both studies—ours and that of Reibman et al. 29 suggest that although biological drug therapies have led to substantial improvements in patients’ quality of life, adjustments in accuracy based on the asthma phenotype are still required.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Our results are in line with a comprehensive evaluation carried out in the United States on complementary therapies with biological drugs in which it was reported that 63% of patients (n = 3262) presented at least one asthma exacerbation per year (M = 1.3). 29 Taken together, both studies—ours and that of Reibman et al. 29 suggest that although biological drug therapies have led to substantial improvements in patients’ quality of life, adjustments in accuracy based on the asthma phenotype are still required.…”
Section: Discussionmentioning
confidence: 80%
“… 29 Taken together, both studies—ours and that of Reibman et al. 29 suggest that although biological drug therapies have led to substantial improvements in patients’ quality of life, adjustments in accuracy based on the asthma phenotype are still required. Our results also showed that at least 38% of the patients need a better assessment of asthma phenotypes and comorbidities.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“… 20 , 21 Unfortunately, approximately 50% of patients with severe asthma are non-eosinophilic and some patients with eosinophilic asthma respond suboptimally to standard therapy and the available biologic therapies or lose control of their asthma after an initial response. 18 , 22 Because of these reasons, discussions with patients on biologic options should occur very early on when first establishing care with asthma specialists. Then, it should continue throughout their lifelong asthma journey, especially if their symptoms are not well uncontrolled.…”
Section: When and Why Should The Discussion About Biologics Occur And...mentioning
confidence: 99%
“…2,4 Some continue to be "difficult to control" despite optimal standard therapy and may benefit significantly from the treatment of biologic agents that target IgE, IL-4 receptor, IL-5, IL-5 receptor, and most recently, TSLP. 18,19 Existing biologic therapies have been found to have a greater response among those with eosinophilic asthma (ie, blood eosinophil count of ≥300 cells/mL). 20,21 Unfortunately, approximately 50% of patients with severe asthma are non-eosinophilic and some patients with eosinophilic asthma respond suboptimally to standard therapy and the available biologic therapies or lose control of their asthma after an initial response.…”
Section: Why Is Shared Decision-making Critical For All Asthmatic Pat...mentioning
confidence: 99%